Mutual Fund Schemes in India and its Types (Large Cap, Mid Cap, Small Cap) - Shubhangi Gore; Tashu Tagade; Arya Arora (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2023)
One of the newest investment instruments on the financial market is mutual fund investing. Concerns about fair returns from various mutual fund schemes are very prevalent among investors. The current study examines the absolute returns of diversified equity funds' large-cap and mid-cap funds over various time periods. 59 large-cap funds and 40 mid-cap funds from various financial institutions have been compiled for various time periods, including 1 day, 1 week, 2 weeks, 1 month, 3 months, and 6 months. Institutions that manage mutual funds are vital to a nation's economic growth. In many industrialised countries, a thriving mutual fund market is the primary driver of economic expansion. India opens its market to various investments in order to offer a wide range of financial products. The performance analysis of mutual funds undertaken by Sharekhan Ltd. is the foundation of this study. In order to invest in bonds, equities, or other sorts of investments, mutual funds use the money from investors. They aid in lowering the investors' transaction costs.Investors don't need to pay attention to the previous performance of mutual funds because it doesn't predict how well they will perform in the future.